PENGARUH INTERVENSI KOMPRES HANGAT AIR REBUSAN BATANG SERAI TERHADAP PENURUNAN NYERI DIMINORE PADA REMAJA BERUSIA 12-21 TAHUN DI ASRAMA DARA JUANTI DI KOTA MALANG - Andriani, Maya Fitri Susi; Wijayanti, Tut Rayani Aksohini; Purwanti, Anik Sri (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
This study aims to evaluate the effect of warm compress intervention with boiled lemongrass stems on reducing dysmenorrhea pain in female adolescents at the Dara Juanti Dormitory in Malang City. This research method uses a pre-experimental research design with one group, using a one-group pretest-posttest design. The total population of female teenagers at the Dara Juanti Dormitory in Malang City was 30 respondents, all of whom experienced desminorrhea pain. The sampling technique used was total sampling. Intervention is carried out by giving a warm compress with boiled lemongrass stems for 15-20 minutes. Data were analyzed using the Wilcoxon paired test. The results showed that the majority of respondents experienced a decrease in desminore pain levels after the intervention. Before the intervention, the majority of respondents experienced moderate pain, but after the intervention, the majority experienced mild pain. Conclusion: Based on data analysis, there is a significant effect between the intervention of warm compresses with boiled lemongrass stems and a reduction in desminore pain in female adolescents at the Dara Juanti Dormitory in Malang City. Therefore, this intervention can be used as an alternative for managing desminorrhea pain in female adolescents.